Implementation of Handling Covid-19 Through The Sendai Framework Approach (West Sumatra Case Study) - Riviwanto, Muchsin; Muslim, Burhan; Wijayantono; Dwiyanti, Defriani (POLTEKKES KEMENKES PADANG, 2024)
Indonesia designated the non-natural disaster Covid-19 as a national in in 2020. The Sendai Framework Agreement (SFA 2015) states that risk reduction efforts must be prioritized, by means of prevention, mitigation and preparedness. West Sumatra Province has disaster management referring to Central Government guidelines from both the BNBP and the Ministry of Health. But it has not yet referred to disaster risk reduction management. The research aims to determine Covid 19 risk management based on the Sendai frame work in West Sumatra Province. The data used is secondary data from research studies of journals and news in chronology. SFA blueprint for predicting the risk of Covid-19 based on Android. The evaluation results of the Covid-19 Risk Prediction Application (M-RCov19) are easy to use and satisfying. Local governments can socialize the M-RCov19 application through focus group discussions (FGD) and training. And it is necessary to issue a policy in the form of a contingency plan (rencon) after the Covid-19 pandemic.